The Effect of SEGU Towards Graphics and Collaborating Skills of High School Students on Reproductive System Material - Intan Inzelia Noor; Yanti Hamdiyati; Widi Purwianingsih (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2021)
The research was motivated by 21st-century developments which made major changes and covered all aspects. Thereby, it was important to master 21st-century skills to be able to deal with these changes. Furthermore, low graphic skills at Senior High School (SHS) level must be considered so they could understand the visual information currently available. Stream Ecology Graphing Unit (SEGU) was a learning strategy to facilitate students to “mind-on” in understanding graph concept. The purpose of the research was to analyze the effect of applying SEGU towards the graphic and collaborating skills of SHS on reproductive material. This research used a Quasi-experimental with Non-Equivalent control group design. The samples were two classes of XI MIPA in an SHS in Bandung which was taken using Purposive sampling. The instruments used were pre-test, post-test, rubrics of measuring collaborating skill, and questionnaires for students’ response towards SEGU. The result showed significant differences between the experimental and control groups in graphic and collaborating and showed intended meaning towards the implementation of SEGU. Most of the students gave a positive response towards SEGU.